ABDOMINAL SUSPENSION OPERATION FOR UTERO-VAGINAL PROLAPSE USING AUTOLOGOUS FACIAL SLING OF RECTUS SHEATH - Nisa, Rahat -un-; Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 2000)
Background: Our purpose was to evaluate the result of abdominal suspension operation using an autologous facial sling for uterovaginal prolapse. Methods: Retrospective case record analysis was performed of total of 16-young patients with low parity at Women and Children Hospital Abbottabad. from 1993-1998. They were followed up to 5 years on an average. Results: All 16 patients except one were successful, two patients got pregnant and had vaginal deliveries without any complication or recurrence. Conclusions: This procedure is less time consuming with negligible blood loss and has good results.